ANALISIS PENGENDALIAN INTERN TERHADAP PENGELOLAAN PERSEDIAAN BARANG PADA CV. BORNEO BANGUN NUSA PALEMBANG - Titi Suelmi; Shelly Farida Tobing (Jurnal RATRI (Riset Akuntansi Tridinanti), 2020)
ABSTRACK            Based on preliminary research, it was stated the problems that were detrimental to CV. Borneo Bangun Nusa Palembang, namely because there are quite a lot of types of goods and equipment that leave and enter the company so that there is a concern that there will be loss, and damage to the stock of goods that are still in storage and consequently CV. Borneo Bangun Nusa Palembang requires better control, namely by carrying out internal controls so that these risks can be prevented.            CV. Borneo Bangun Nusa Palembang is a company that really needs internal control that can secure its assets and is able to carry out supervisory activities within the company environment, so with the number of transactions related to internal control and inventory management, the company must be able to implement effective internal control and inventory management. efficient and minimize errors Keywords : Internal Control, Inventory management, Effective